(untitled) (Práxis Educativa, 2025)
This study aimed to analyze the strategic plans of Brazilian Graduate Programs in the field of Education, identifying the conceptions, actors, and regulatory processes involved in self-assessment, with the goal of problematizing the reconfigurations resulting from the culture of performativity. Twelve documents were analyzed using content analysis. It was concluded that self-assessment, although advocated in the literature and in the conceptualizations of strategic planning as a collective process of self-analysis, participatory learning, inquiry, and reflection, may have been driven by the evaluation policy of the Coordination for the Improvement of Higher Education Personnel (CAPES) and risks being reduced, within the programs, to the implementation of performative re-regulation policies. Keywords: Self-assessment. Strategic planning. Graduate education.